2016
DOI: 10.1002/mrm.26309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transcytolemmal water exchange on estimates of tissue microstructural properties derived from diffusion MRI

Abstract: Purpose To investigate the influence of transcytolemmal water exchange on estimates of tissue microstructural parameters derived from diffusion MRI using conventional PGSE and IMPULSED methods. Methods Computer simulations were performed to incorporate a broad range of intracellular water life times τin (50 – ∞ ms), cell diameters d (5 – 15 μm), and intrinsic diffusion coefficient Din (0.6 – 2 μm2/ms) for different values of signal to noise ratio (10 to 50). For experiments, murine erythroleukemia (MEL) canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 52 publications
5
72
0
Order By: Relevance
“…However, recent studies have found the accuracy of the measurements of f in are significantly affected by k in themselves. A recent study [40] reports that f in values obtained from either quantitative PGSE (pulsed gradient spin echo) [41] or OGSE (oscillating gradient spin echo) [42, 43] diffusion sequences are significantly underestimated due to transcytolemmal water exchange, while fitted cell size values are less influenced. Another study found out that “DCE-MRI is not a reliable biomarker of extracellular space for a range of physiological conditions” confirmed with histology analysis [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have found the accuracy of the measurements of f in are significantly affected by k in themselves. A recent study [40] reports that f in values obtained from either quantitative PGSE (pulsed gradient spin echo) [41] or OGSE (oscillating gradient spin echo) [42, 43] diffusion sequences are significantly underestimated due to transcytolemmal water exchange, while fitted cell size values are less influenced. Another study found out that “DCE-MRI is not a reliable biomarker of extracellular space for a range of physiological conditions” confirmed with histology analysis [44].…”
Section: Discussionmentioning
confidence: 99%
“…Exchange of water across the sphere wall is another unmodeled effect that may contribute to bias in R and f i . As longer diffusion times are expected to increase sensitivity to exchange, it may be hypothesized that, depending on the rate of exchange, excluding the longest diffusion time data from the fitting would reduce such sensitivity and therefore improve the accuracy of R .…”
Section: Discussionmentioning
confidence: 99%
“…The measured DWI signal S is shown by Equation :S=vitalicin·Sitalicin+false(1-vinfalse)·Sitalicexwhere S in , and S ex are the signal magnitudes per volume from the intra‐ and extracellular spaces, respectively, and v in is intracellular water fraction. Note that water exchange between intra‐ and extracellular spaces is ignored, but does not affect the estimation of mean cancer cell size, although it may bias the estimation of cell density …”
Section: Methodsmentioning
confidence: 99%
“…All MRI measurements of cells in vitro were performed on a Varian/Agilent 4.7T MRI spectrometer (Agilent Technologies, Santa Clara, CA) similar to the approach described previously . A 2‐mm‐thick slice crossing the center of each cell pellet was imaged with a field of view (FOV) 16 × 16 mm and a matrix size 64 × 64, yielding a spatial resolution of 250 μm.…”
Section: Methodsmentioning
confidence: 99%